Penerapan Kebijakan Formulatif Pengaturan Pembuktian Terbalik Tindak Pidana Korupsi Gratifikasi - Misael Asarya Tambunan (MLJ Merdeka Law Journal, 2022)
This study aims to examine the formulative policy of reversing the provision of proof of the crime of graft corruption in the ius constitutum or positive law in Indonesia and the ius constituendum policy or future law in Indonesia. This research is a normative legal research. The results of the study show that the formulative policy for reversing proving of corruption in the ius constitutum or positive law in Indonesia is regulated in Article 12B of Law No. 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning Eradication of Corruption Crimes does not yet reflect justice and legal certainty. Article 12B 12B Law No. 20 of 2001 concerning Amendment to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes which regulates Gratification is contrary to Article 27 paragraph (1) of the 1945 Constitution. This is related to the principle of equal rights. Likewise, the formulation of the Norms Article 12 B Paragraph (1) is contrary to the provisions of Article 37 of the Corruption Crime Act.DOI: https://doi.org/10.26905/mlj.v3i2.9261